Effectiveness of Front-End Engineering (FEE) in Construction Industry in Malaysia - Tow Kai Xuen,; Noor Yasmin Binti Zainun, (Recent Trends in Civil Engineering and Built Environment, 2022)
Throughout of a construction project’s life cycle, Front-End Engineering (FEE) is an engineering design approach used to control project expenses and thoroughly plan a project before a fix bid quote is submitted and start of construction phase. FEE lead to a minimum risk of construction project since it practice a pre-project planning and feasibility analysis. This study is conducted to establish effectiveness of FEE application in construction industry in Malaysia. Questionnaire was created based on the extensive literature review. There are nine aspects of FEE that have been selected based on previous studies to establish the effectiveness of FEE in construction industry in Malaysia. From the data collection from questionnaire, it will be using a statistical software to analyze the data which is Statistical Package for the Social Sciences (SPSS) for the reliability analysis. Next, Principal Component Analysis (PCA) which adopted from SPSS is use to determine the significant and correlative effectiveness FEE aspects. According to the PCA analysis, three principal components were chosen out of nine principal components since the total variance of the eigenvalues was more than one. As the results the most correlative and significant effectiveness aspects in FEE in Malaysia are (1) constructability, (2) risk analysis and (3) project scope. However, the others FEE aspects were evaluated, but their effects on the analysis were minimal in comparison to the three chosen highest significant FEE aspects. It is intended that this study would benefit other academics and that the outcome would assist construction industry operators in planning and improving their FEE practices.